2010
DOI: 10.1590/s0103-64402010000500014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the panoramic image formation in different anatomic positions

Abstract: The aim of this study was to determine size, shape and position of the image layer by evaluation of the radiographic image formation in different anatomic positions. A customized phantom was made of a rectangular acrylic plate measuring 14 cm² and 0.3 cm thick, with holes spaced 0.5 cm away and arranged in rows and columns. Each column was separately filled with 0.315 cm diameter metal spheres to acquire panoramic radiographs using the Orthopantomograph OP 100 unit. The customized phantom was placed on the men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…Hayakawa et al 24 reported the greatest distortions in the midline region. In the present study, the results were similar to those mentioned above 20,24 because the horizontal measurements in the incisor regions were also taken on both sides of midline in the radiographs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Hayakawa et al 24 reported the greatest distortions in the midline region. In the present study, the results were similar to those mentioned above 20,24 because the horizontal measurements in the incisor regions were also taken on both sides of midline in the radiographs.…”
Section: Discussionsupporting
confidence: 88%
“…These results could be related to the sample used, which by the mandibular shape established a specific position within the image layer of the X-ray machine. 20 Considering the independent analyses of vertical measurements, each region produced a different magnification, shown to be greater in the anterior and smaller in the posterior regions, similar to the results found in previous studies. 11,21 However, Sameshima and Asgarifar 16 observed the smallest magnification in the anterior and the greatest in the posterior region.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Since its introduction to the dental practice by Paatero in 1952, it has become an important diagnostic tool (Choi, 2011;Ladeira et al, 2010). The images that offers, allows us an overview of the maxillary structures and its teeth relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Various parameter's evaluation and various system's ranking based on mosaic creation were proposed in literature like ranking of orientation tracking systems [9], ranking of electrooptical (EO) systems [10], Radiographic Quality [11], ranking of radiographic digital system [12], quality of size, shape and position of the image layer in radiographic panoramic images [13], quality of video compression [14] and ranking of tracking methods [15].…”
Section: Introductionmentioning
confidence: 99%